Struktur Linguistik Bahasa: Kajian Fonologi dan Morfologi dalam Tuturan Anak Usia Dini - Ana tiara Isnaeni; Nasywa Afiffah; Silvina Noviyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The phonological and morphological development of early childhood often exhibits sound errors, word simplifications, limited vocabulary, and differences in ability due to environmental factors. Research is needed to understand how the language acquisition process occurs and what factors influence the quality of children's language development. This study used a qualitative method with a literature study approach. Data were collected from scientific journals, linguistics books, academic articles, and relevant research reports. Analysis was conducted descriptively and qualitatively through reading, grouping data, comparing theories, and drawing patterns of children's phonological and morphological development. The results of the study indicate that children experience gradual phonological development from prelinguistic to phoneme mastery, accompanied by natural errors such as syncope, apheresis, and sound substitution. In morphology, children begin to master basic morphemes, affixation, reduplication, and the dominance of the noun lexicon. The environment has been shown to be a major factor in language acquisition. The study concluded that children's phonological and morphological development is strongly influenced by environmental stimulation, verbal interaction, and cognitive maturity. It is recommended that parents and educators provide a language-rich, responsive environment and regularly provide verbal stimulation to optimize children's language development.